An Embodied Tutoring System for Literal vs. Metaphorical Concepts - Sionti, Marietta; Schack, Thomas; Aloimonos, Yiannis (Frontiers in Psychology, 2018)
• In this paper we combine motion captured data with linguistic notions in a game-like intelligent tutoring system, in order to help elementary school students to better differentiate literal from metaphorical uses of motion verbs, based on embodied information. In addition to the thematic goal, we intend to improve young students’ attention and spatiotemporal memory, by presenting sensorimotor data experimentally collected from thirty two participants in our motion capturing labs. Furthermore, we examine the accomplishment of game’s goals and compare them to curriculum’s approach. Sixty nine elementary school students were randomly divided in two experimental groups (game and traditional) and one control group, which did not undergo any intervention. All groups were tested in pre and posttests. Even though the diagnostic pretests present a uniform picture, two way analysis of variance suggests that the experimental groups showed progress in posttests and, more specifically, game group remarkably progressed in the verbs/actions presented during the intervention. Furthermore, in the game condition the participants needed gradually shorter period of time to identify the avatar’s actions. This finding was considered as a first indication of attentional and spatiotemporal memory’s improvement, while the game’s assistance features cultivated students’ metacognitive perception.